2014
DOI: 10.3329/cmoshmcj.v13i2.21071
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnetic Resonance Imaging in the Diagnosis of Cervical Disc Herniation: Comparison with Peroperative Findings

Abstract: to evaluate the role of Magnetic Resonance Imaging in the diagnosis of cervical disc herniation. A total of 40 patients having clinical features of cervical disc herniation with neck pain referred to the Department of Radiology & Imaging for MRI of their cervical spine were included in the study. At first all the patients were evaluated by detail history and clinical examination with special emphasis on clinical features. Then subsequently MRI of cervical spine was performed in all cases. The MRI report was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Spinal stenosis following spinal disk herniation is one of the main causes of neurosurgeon surgeries at high ages and is an important etiologic factor in the occurrence of pain and disability in these individuals [20], [47], [48]. Morshed et al, in a study with a sample of 48 patients, reported about six cases of stenosis induced by lumbar disk herniation, of which one was partial stenosis and six cases were complete stenosis [49]. In our study, the highest prevalence of stenosis was in L4-L5 lumbar levels, which accounts for 38 cases (61.15%) of all stenosis cases.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal stenosis following spinal disk herniation is one of the main causes of neurosurgeon surgeries at high ages and is an important etiologic factor in the occurrence of pain and disability in these individuals [20], [47], [48]. Morshed et al, in a study with a sample of 48 patients, reported about six cases of stenosis induced by lumbar disk herniation, of which one was partial stenosis and six cases were complete stenosis [49]. In our study, the highest prevalence of stenosis was in L4-L5 lumbar levels, which accounts for 38 cases (61.15%) of all stenosis cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the cervical region, it occurs more commonly in the postrolateral (2). The herniated disc can take the form of protrusion, extrusion and sequestration (2). When disc fragment is connected to intervertebral disc and contain Annulus, not connected to intervertebral disc and only contain posterior longitudinal ligament (PLL) and when is free within spinal canal called protrusion, extrusion and sequestration, respectively (2).…”
Section: Background and Importancementioning
confidence: 99%
“…Disc herniation is defined as the prolapsed of material disc into the spinal canal (2). In the cervical region, it occurs more commonly in the postrolateral (2). The herniated disc can take the form of protrusion, extrusion and sequestration (2).…”
Section: Background and Importancementioning
confidence: 99%
See 2 more Smart Citations